2011
DOI: 10.1143/jjap.50.06gh01
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic MnAs Nanocluster Composites Position-Controlled on GaAs (111)B Substrates toward Lateral Magnetoresistive Devices

Abstract: We describe a versatile portable prototype device for electrical measurements of ''soft'' materials. It consists of a custommade micromanipulator and a gas-tight syringe to hold a mercury mini-drop to make reliable and controllable electrical contacts with solid-state materials of interest. Compared with the conventional method (deposition of thin metal films under vacuum), the proposed experimental approach is simpler and more cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Thus, the cluster growth only took place in mask openings intentionally prepared, making it possible to actively tune the clusters' size, shape, and position [25][26][27][28]. Figure 1 shows scanning electron microscopy images of the two nanocluster arrangements prepared.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the cluster growth only took place in mask openings intentionally prepared, making it possible to actively tune the clusters' size, shape, and position [25][26][27][28]. Figure 1 shows scanning electron microscopy images of the two nanocluster arrangements prepared.…”
Section: Resultsmentioning
confidence: 99%
“…SA-MOVPE is based on the bottom-up formation of single-crystalline ferromagnetic MnAs NCs on defined sites of semiconducting substrates. The SA-MOVPE is promising as it enables us to accurately adjust the size, shape, number, position, and spatial arrangement of the MnAs NCs [16][17][18][19] within the hybrids to tune its magnetic and magnetotransport properties. 3,[20][21][22] Ordered planar arrangements of coupled NCs show large MR effects 23 and MR ratios of 300% are predicted by theory.…”
mentioning
confidence: 99%
“…The insets show two types of typical NCs marked "A" and "B." In our previous study on the SA-MOVPE of MnAs NCs on GaAs(111)B substrates, 18 it was found that the hexagons of the NCs, which arise from the hexagonal NiAs-type crystal structure, were always rotated by 30 against those of the AlGaAs buffer layers underneath. The corresponding hexagonal nanodisk structure of the AlGaAs buffer layers exhibits six equivalent {0-11} side-wall facets.…”
mentioning
confidence: 99%
“…17,18 Besides a high structural quality, this method offers the possibility to precisely control the position of the nanoclusters as well as their size and shape. [18][19][20] The MnAs nanoclusters grown by SA-MOVPE show a magnetization orientation in the sample plane with an in-plane anisotropy which can be tuned by the clusters' shape. [19][20][21] These magnetic properties, a relatively high Curietemperature of about 340 K (Refs.…”
mentioning
confidence: 99%
“…[18][19][20] The MnAs nanoclusters grown by SA-MOVPE show a magnetization orientation in the sample plane with an in-plane anisotropy which can be tuned by the clusters' shape. [19][20][21] These magnetic properties, a relatively high Curietemperature of about 340 K (Refs. 22 and 23) as well as the advantage to control their position accurately make the MnAs nanoclusters grown by SA-MOVPE ideal building blocks for planar magneto-nanoelectronic device structures even for room temperature applications.…”
mentioning
confidence: 99%